Reasons for omission of enforcement of an administrative judge's verdict and means of legal protection - Alen Rajko (Zbornik Radova Pravnog Fakulteta u Splitu, 2015)
Besides general repercussions of an omission of enforcement of court decisions on the protection of the rights of the parties and on the functioning of the legal system, such an omission in the administrative dispute has additional implications, related primarily to the realization of the constitutional guarantee of judicial review of administrative decisions, the concept of separation of powers, construction of a democratic state, etc. After general considerations of the matter of enforcement of court decisions, the author analyzes the normative framework of the enforcement of judgments of the administrative courts, as well as the evolution of this framework, points out the open questions regarding mentioned regulation, as well as the means of legal protection in case of an omission of enforcement of the verdict.